Nyelvi diszkrimináció és előítéletesség kárpátaljai magyartanároknál - Jánk István (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
A magyar anyanyelvi nevelés akárcsak Magyarországon, Kárpátalján sem problémamentes. A témával kapcsolatos problémák közül számos nyelvi természetű van, melyek közül egy – oktatási és nyelvészeti szempontból – kiemelt jelentőségűvel foglalkozom a továbbiakban. Jelen tanulmány egy nyelvi diszkriminációt vizsgáló, négy országon átívelő kutatás kárpátaljai magyarságot érintő részeredményeiről kíván beszámolni. Arról, hogy a vizsgálatba bekapcsolódó kárpátaljai leendő és gyakorló magyartanárok mennyire előítéletesek nyelvileg, milyen mértékben diszkriminálnak nyelvi alapon, illetve hogy mindez a többi ország magyartanárainak eredményeivel összevetve men - nyire számít jelentősnek.

Abstract. Teaching Hungarian language as a mother tongue in Transcarpathia is not going without problems, similarly to the situation in Hungary. There are many language-related issues in the topic, the problem which I deal with is of great importance mainly in education and linguistics. The current paper aims to report the results of a research on language discrimination in four countries focusing only on the results of Transcarpathia. The study highlights how prejudiced the practicing teachers and teacher trainees of Hungarian language in Transcarpathia are linguistically towards their students. Moreover, the data show to what extent they discriminate on a linguistic basis and how significant this phenomenon is in comparison to the results of the Hungarian language teachers of other countries.

Резюме. Виховання корінних угорців, на жаль, не обходиться без проблем як в Угорщині, так і на Закарпатті. Серед цих труднощів багато перебувають саме у мовній сфері. Зокрема, це освіта і навчання, на якій зосереджена увага нашого дослідження. У ньому зроблено спробу вивчення мовної дискримінації на основі результататів анкетування, котрі проводилися у чотирьох країнах, що охоплюють поселення карпатських угорців. Більше того, виходячи з результатів анкетування, було з'ясовано наскільки перспективними є угорські викладачі у своєму мовленні, а також те, якою мірою вони використовують дискримінацію на мовній основі і наостанок, наскільки це є важливо у порівнянні з результатами угорських викладачів з інших країн.
Language Discrimination and Prejudice of Teachers of Hungarian in Transcarpathia
Мовна дискримінація і упередження стосовно угорських вчителів Закарпаття
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008907
Keywords: nyelvi diszkrimináció; nyelvi előítélet; lingvicizmus; magyartanárok